Excited States Versus Reaction Intermediates as Active Species in Photoinduced Redox Reactions of Cyrhetrenyl and Ferrocenyl Chalcones: A 351 Nm Flash Photolysis Study - Godoy-Gonzalez, F; Godoy-Gonzalez, F; Maldonado-Hernandez, T; Maldonado-Hernandez, T (American Chemical Society, 2019)
The photoinduced redox reactions of two organometallic chalcones: trans, E, (η5-C5H4C(O)CH=CH-4-benzo-15-crown-5)Re(CO)3, 1, and trans, E, (η5-C5H4C(O)CH=CH-4-benzo-15-crown-5)Fe(η5-C5H4C(O)CH=CH-4-benzo-15-crown-5), 2, were investigated in fluid solution using the flash photolysis technique. For a better understanding of the photoinduced redox processes of these organometallic chalcones, an electron donor, triethylamine (TEA), and an electron acceptor, methylviologen dichloride (MVCl2), were chosen. Two parallel reaction paths for the decay of the intermediate 1-I, that is, the anion radical of 1, were observed in the presence of TEA. One generates a radical anion, while the other reaction path produces the Z isomer. Instead, the photoinduced reaction of 2 with TEA in MeOH generates an intense absorption band at λmax = 660 nm, which is attributed to a 2-I·MeOH adduct. The oxidative process between 1-I and MV2+ in CH3CN generates transient spectra consistent with the formation of the radical cation MV•+. In contrast, the photoinduced reaction between 2 and MV2+ showed that the generation of MV•+ occurs through a complex mechanism. MV•+ is formed in two steps where the first one is the formation of an adduct between the long-lived metal-to-ligand charge transfer (MLCT)Fe→Chalcone excited state and MV2+. These results have shown that intermediates 1-I and 2-I can function as photo-oxidants and photoreductants better than the chalcone short-lived excited states. Copyright © 2019 American Chemical Society.